Aktivitas Antibakteri Ekstrak Daun Bidara (Ziziphus mauritiana) terhadap Pertumbuhan Staphylococcus aureus pada Isolat Ulkus Diabetikum - Rima Via Angraini; Adinugraha Amarullah; Carisa Salsabilla Wiyantie; Lisa Revalina; Christine Amanda Novitri (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Diabetes mellitus is a long term metabolic disease that may trigger various complications, including diabetic ulcers. These ulcers are highly vulnerable to bacterial infection, especially by Staphylococcus aureus, which can delay wound healing and worsen the patient’s condition. This study was conducted to determine the antibacterial activity of ethanol extract of bidara leaves (Ziziphus mauritiana L.) against Staphylococcus aureus isolated from diabetic ulcer wounds. The research employed an experimental laboratory design using the well diffusion technique on Mueller Hinton Agar media. Bidara leaf extract was tested at concentrations of 5%, 10%, and 15%. Chloramphenicol was applied as the positive control, while DMSO and distilled water were used as negative and neutral controls. Antibacterial effectiveness was assessed based on the diameter of the inhibition zone formed around each well. The findings demonstrated that the ethanol extract of bidara leaves was able to inhibit the growth of Staphylococcus aureus at all tested concentrations. The strongest inhibitory effect was observed at the 15% concentration. Statistical evaluation using one way ANOVA revealed a significant difference between treatment groups (p<0.05). The antibacterial activity is thought to be associated with the presence of bioactive compounds, including flavonoids, alkaloids, tannins, and saponins, which may interfere with bacterial cell function and growth. In summary, ethanol extract of bidara leaves shows promising potential as a natural antibacterial agent against Staphylococcus aureus isolated from diabetic ulcers.